(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, the State Committee for Veterinary and Livestock Development, the Ministry of Higher and Secondary Special Education, the Samarkand Institute of Veterinary Medicine of the Ministry of Economic Development and Poverty Reduction further improve the system of training highly qualified personnel in the field of veterinary and animal husbandry. Samarkand State University of Veterinary Medicine, Animal Husbandry and Biotechnology (hereinafter - the University).